2016
DOI: 10.1360/n972016-00646
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency eco-agriculture model obtain both larger yield and economic benefit: A case study in Hongyi Organic Farm

Abstract: Fluorination vs. chlorination: a case study on high performance organic photovoltaic materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…). Some other studies also demonstrated that effective pest control can be achieved using insect‐trapping lamps . A consecutive 6‐year study showed that both daily and annual average fresh weights of trapped pests decreased substantially with each passing year, with the average daily fresh weight of trapped pests declining from 0.45 kg day −1 in 2009 to 0.012 kg day −1 in 2014, and the annual total fresh weight of trapped pests decreasing by 93.8% .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…). Some other studies also demonstrated that effective pest control can be achieved using insect‐trapping lamps . A consecutive 6‐year study showed that both daily and annual average fresh weights of trapped pests decreased substantially with each passing year, with the average daily fresh weight of trapped pests declining from 0.45 kg day −1 in 2009 to 0.012 kg day −1 in 2014, and the annual total fresh weight of trapped pests decreasing by 93.8% .…”
Section: Discussionmentioning
confidence: 95%
“…The peasant farmers in this region still prefer to use pesticides to eliminate these pests, and several pesticides are widely used, including phoxime, imidacloprid, avermectin and lambda‐cyhalothrin, so the dosages and application frequencies of these pesticides are still increasing. In the last decade, researchers have found that physical methods, in particular use of insect‐trapping lamps, can capture most of the pests in open crop systems . When insects are trapped in these lamps, the eggs of the captured females cannot develop into larvae, and so use of pesticides can be greatly reduced because there are fewer pests and the ecological balance is restored.…”
Section: Introductionmentioning
confidence: 99%
“…(1) 农户生产总投入(farmer total cost) [51] , 农户作为施肥主体, 增产依靠化肥投入 [52] , 夏 河地区化肥产出率最高, 增加化肥投入有利可图, 而 通渭地区和渭源地区, 长期以种植为主, 化肥产出率 低, 两地化肥产出率为7%左右, 家畜系统有机粪肥 未进入作物生产, 限制了作物生产和家畜生产的有 效耦合. 黄土高原向青藏高原过渡生态带环境复杂, 而草地资源和生态环境是公共产品, 具有非排他性, 农户追求自身效益容易产生"搭便车"现象, 故减少 化肥投入 [52] 、加强植物生产层和动物生产层耦合 [53] 、 寻求农业生态系统的自我调节零界点 [54] 和优化农户 占比等措施, 对实现生态效益和经济效益双重目标 表 7 综合系统农户占比与经济生产行为的Logistic回归方程 尤为重要.…”
Section: 数据分析unclassified
“…As cultivated land hardens, the soil becomes less suitable for crops, resulting in critically degraded crop growth, Sustainability 2023, 15, 6801 2 of 11 production, and quality [11,12]. Jing measured the compression and water characteristic curves of brown soil in the Shenyang area and the distribution of the soil hardness profile and water infiltration rate in compacted brown soil [13]. Wang studied the effect of organic matter addition on the acidity and yield of paddy soil [14].…”
Section: Introductionmentioning
confidence: 99%